2021
DOI: 10.3390/biom11030387
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Toxic AGEs (TAGE) Triggers Numerous Types of Cell Damage

Abstract: The habitual intake of large amounts of sugar, which has been implicated in the onset/progression of lifestyle-related diseases (LSRD), induces the excessive production of glyceraldehyde (GA), an intermediate of sugar metabolism, in neuronal cells, hepatocytes, and cardiomyocytes. Reactions between GA and intracellular proteins produce toxic advanced glycation end-products (toxic AGEs, TAGE), the accumulation of which contributes to various diseases, such as Alzheimer’s disease, non-alcoholic steatohepatitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 131 publications
1
40
0
Order By: Relevance
“…Based on these findings, we refer to the AGEs recognized by the anti-TAGE antibody as toxic AGEs (TAGE). Increased TAGE levels were found to correlate with various lifestyle diseases, such as non-alcoholic steatohepatitis, DM, cancer, dementia, infertility, and cardiovascular diseases [ 22 , 23 , 24 ]. An analysis of the toxicity of TAGE in the liver, a major site for the metabolism of excess glucose and fructose, revealed that the accumulation of TAGE was associated with damage to cell function and the induction of cell death, ultimately leading to liver disease [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, we refer to the AGEs recognized by the anti-TAGE antibody as toxic AGEs (TAGE). Increased TAGE levels were found to correlate with various lifestyle diseases, such as non-alcoholic steatohepatitis, DM, cancer, dementia, infertility, and cardiovascular diseases [ 22 , 23 , 24 ]. An analysis of the toxicity of TAGE in the liver, a major site for the metabolism of excess glucose and fructose, revealed that the accumulation of TAGE was associated with damage to cell function and the induction of cell death, ultimately leading to liver disease [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Defense against glycation damage in mitochondria and plastids. The glycating agents MGO and GO are produced spontaneously during sugar metabolism and lipid peroxidation, so that all organisms need to defend against the ensuing damage 34,35 . The main pathway of MGO detoxification is the glyoxalase system comprised of glyoxalases 1 and 2 (I and II in plants) and glutathione 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased consumption of sugars, especially fructose, and AGE-enriched diets are related to the generation of intracellular AGEs that induce lipogenesis and inflammation in crosstalk with ER stress [ 125 ]. Besides, the extravasation of AGEs and its interaction with RAGE is associated with the development and evolution of several chronic diseases, including steatosis and CVD [ 126 ]. A recent meta-analysis found an association among elevated levels of several types of AGEs with NAFLD [ 127 ] and the determination of fluorescent AGE has been considered as a potential biomarker for NAFLD stratification [ 128 ].…”
Section: Ages Er Stress and Inflammation In Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%